Recovery of the Intestinal Microbiota Metabolic Activity in Patients with Bronchial Asthma - O. Yu. Zolnikova; N. D. Potskhverashvili; N. I. Kokina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To investigate the feasibility of correcting the content and profile of short-chain fatty acids (SCFA) in feces of patients suffering from allergic bronchial asthma.Materials and methods. The study included 30 patients with allergic bronchial asthma (BA). All patients underwent a generally accepted range of clinical laboratory tests, functional respiratory tests and a hydrogen breath test with lactulose to detect SIBO. The SCFA spectrum was determined by gas-liquid chromatographic analysis. All patients with BA underwent standard basic therapy with combined preparations containing long-acting beta-2-adre nergic agonists and inhaled glucocorticoids. For the treatment of SIBO, 10 patients were prescribed rifaximin-α at a dose of 200 mg × 3 times a day for 7 days, 10 patients were prescribed rifaximin-α at the same dose, followed by the administration of the Lactobalans drug containing at least 3.0×109 CFU/caps. probiotic microorganisms (Lactobacillus gassery KS-13, Lactobacillus gasser LAC-343, Lactobacillus ramnosus LCS-742, Bifi dobacterium bifi dum G9-1, Bifi dobacterium longum MM-2, Bifi dobacterium longum BB536 Strain M, Bifi dobacterium biumidum BB536 Strain M. Bifi dobacterium biumidum biumidum BB536 Strain M. lactis B1-04) in 1 capsule once a day for 1 month. A probiotic course of 1 month was assigned to 10 patients without SIBO as part of the complex treatment of BA. The study of SCFA was carried out in all groups immediately after the end of probiotic therapy (after 1 month).Results. All patients demonstrated normalisation of the SCFA spectrum and anaerobic index. In patients without SIBO, during a probiotic therapy, an increase in the total content of SCFA (p <0.001), acetic and butyric acid (p <0.001) was revealed. The administration of a probiotic after a course of rifaximin-α led to a decrease in the relative amount of isoacids and the isoacids/acids ratio in comparison with patients who received rifaximin-α only for treatment of SIBO (p <0.05).Conclusion. The obtained results demonstrate the potential of drugs in affecting the composition and number of active bacterial metabolites of the intestinal biotope, which indicates the restoration of intestinal microbiocenosis.